Sexism and human enhancement - Sparrow, Robert (Journal of medical ethics, 2013)
Given the morally disastrous history of eugenics, one might have thought that contemporary advocates of genetic human enhancement would be especially mindful of the historical resonances of the arguments they put forward. Two aspects of Paula Casal's defence of enhancement against my recent criticisms are therefore more than a little surprising.1i First, her hypothetical case for sex selection for ‘moral enhancement’ relies on claims drawn from sociobiology and evolutionary psychology, which are at best controversial and at worst represent pseudo-scientific rationalisations for contemporary social prejudices. Second, despite her protestations, her fundamental objection to my original point—that advocates of enhancement are committed by the logic of their argument to the conclusion that parents should choose girl children—relies upon the idea that parents have a moral obligation to have children that will serve the interests of the nation rather than will have the best expected welfare. This is a long way from Savulescu's2 original argument for ‘procreative beneficence’ and opens the door to a whole series of politically dangerous arguments for a Brave New World. I will expand on these observations below. Let me begin, however, with some necessary clarifications and qualifications of the argument that Casal takes herself to be criticising and by offering rebuttals to four of her minor claims. I was not setting out, in the papers to which Casal is responding, to defend the therapy/enhancement distinction because I thought it was an unproblematic notion. I am well aware of the many difficulties with drawing the line between therapy and enhancement and—perhaps more importantly—explaining why it has any moral significance. I simply pointed out that abandoning the therapy/enhancement distinction has unanticipated and counterintuitive consequences when it comes to sex selection. Given the longer life expectancy of women—and the intuition that parents should bracket concerns about the …